Pengaruh Kualitas Produk, Harga dan Citra Toko Terhadap Keputusan Pembelian - Ika Diah Saputri; Moh Agung Surianto (Journal of Business and Economics Research (JBE), 2023)
This study aims to study consumer behavior through purchasing decisions, in this study identifying product quality factors, price perceptions, store image, which in the literature study this factor influences purchasing decisions. This research is a type of quantitative research with a sample size of 100 respondents, the data is obtained through a questionnaire distributed with the provisions of consumers who have bought products or visited the aji jaya makmur Gresik store, the analysis used in this study is multiple linear regression which will further test the hypothesis. The results showed that product quality has a positive effect on purchasing decisions at Toko Aji Jaya Makmur where the results show a significance level of 0.000 <0.05 and a significance value smaller than 0.05 and t count 4.254 greater than t table 1.984. Price Perception has a positive effect on purchasing decisions at Toko Aji Jaya Makmur where the variable t value found a significance level of 0.019 <0.05 and a significance value smaller than 0.05 t count 2.382 greater than t table 1.960. Meanwhile, store image has no effect on purchasing decisions at Toko Aji Jaya Makmur where the significance level is 0.864 greater than 0.05. t count 0.864 is smaller than t table 1.984 and the significance value is greater than 0.05, based on these findings, it shows that product quality has a dominant influence on purchasing decisions, so it is important for Aji Jaya Makmur Gresik stores to always pay attention to the quality of their products to keep consumers from switching to competitors.